An environmentally friendly process for the recovery of valuable metals from spent refinery catalysts. Issue 6 (June 2013) - Rocchetti, Laura; Fonti, Viviana; Vegliò, Francesco; Beolchini, Francesca
The present study dealt with the whole valorization process of exhaust refinery catalysts, including metal extraction by ferric iron leaching and metal recovery by precipitation with sodium hydroxide. In the leaching operation the effects on metal recovery of the concentration and kind of acid, the concentration of catalyst and iron (III) were determined. The best operating conditions were 0.05 mol L −1 sulfuric acid, 40 g L −1 iron (III), 10% catalyst concentration; almost complete extraction of nickel and vanadium, and 50%extraction efficiency of aluminium and less than 20% for molybdenum. Sequential precipitation on the leach liquor showed that it was not possible to separate metals through such an approach and a recovery operation by means of a single-stage precipitation at pH 6.5 would simplify the procedures and give a product with an average content of iron (68%), aluminium (13%), vanadium (11%), nickel (6%) and molybdenum (1%) which would be potentially of interest in the iron alloy market. The environmental sustainability of the process was also assessed by means of life cycle assessment and yielded an estimate that the highest impact was in the category of global warming potential with 0.42 kg carbon dioxide per kg recovered metal.